Effectiveness of Object Relation Approach on Ego Strength and Communicational Patterns among Married Women with Breast Cancer - Kabiri, Mahsa; Bazzazian, Saeideh; Amirimajd, Mojtaba; Ghamari, Mohammad (International Journal of Applied Behavioral Sciences, 2018)
Introduction: The purpose of this study was to investigate the effectiveness of object relation approach on ego strength and communicational patterns among married women with breast cancer. Method: The present experimental study included pre-test, post-test with the control group design. The statistical population of this study consisted of all 40-60 years old women with breast cancer in Tabriz. Thirty people were selected by sampling method and were randomly placed in both experimental and control groups. The Instruments used in this study were psychological inventory of ego strength (PIES) and Christensen and Suhhaway communicational patterns questionnaire (CPQ). The experimental group received object relations training for six 90-minutes sessions, one session in a week. Analysis of the data was done using descriptive and inferential tests such as covariance analysis was conducted. Results: The findings showed that difference between two groups of the experimental and control one was significant in terms of ego strength (p<0.001) and mutual constructive patterns (p<0.001) . Conclusion: Based on the results, the object relation approach has a significant impact on the modulation of the ego's strength, by modifying and improving the defense mechanisms of the patients. Also this approach improves the communication patterns of women with breast cancer. They were able to communicate more mature with the spouse and family thus they were able to improve their communication patterns. Object relation approach can be used in similar cases.